2022
DOI: 10.1101/2022.06.29.498105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trim-Away degrades lysine-less substrates without requiring ligase autoubiquitination

Abstract: TRIM proteins are the largest family of E3 ligases in mammals. They include the intracellular antibody receptor TRIM21, which is responsible for mediating targeted protein degradation during Trim-Away. Despite their importance, the ubiquitination mechanism of TRIM ligases has remained elusive. Here we show that while TRIM21 activation results in ubiquitination of both ligase and substrate, autoubiquitination is regulatory and not required for substrate degradation. Substrate binding stimulates N-terminal RING … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Thus, the results of both reports do not preclude our conclusions, which are based on a methodology that allows us to show that the lysine-deficient proteins can undergo non-lysine ubiquitination and proteasomal degradation independent of ubiquitination. Supporting this assumption, recent Trim-Away assay results showed that the TRIM21 E3 efficiently degrades lysine-less substrates, potentially in tandem with a non-canonical ubiquitination mechanism 73 . This suggests that UPS may recruit specialised E3s that control the abundance of lysine-deficient proteins.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the results of both reports do not preclude our conclusions, which are based on a methodology that allows us to show that the lysine-deficient proteins can undergo non-lysine ubiquitination and proteasomal degradation independent of ubiquitination. Supporting this assumption, recent Trim-Away assay results showed that the TRIM21 E3 efficiently degrades lysine-less substrates, potentially in tandem with a non-canonical ubiquitination mechanism 73 . This suggests that UPS may recruit specialised E3s that control the abundance of lysine-deficient proteins.…”
Section: Discussionmentioning
confidence: 95%
“…Upon binding virus:antibody complexes, the RING domain becomes active, and promotes autoubiquitination of TRIM21 with the synthesis of K63-linked ubiquitin chains. Antibody and antibody-bound targets may also become ubiquitinated by TRIM21, consistent with an urgent and acute danger signal that intracellular antibody-opsonised particles represent (Kiss et al, 2022;Mevissen et al, 2023).…”
Section: Introductionmentioning
confidence: 85%